2023
DOI: 10.1007/s40948-023-00627-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the influence on mechanical properties and acoustic emission characteristics of granite after heating and water-cooling cycles

Abstract: This study explores explore the failure characteristics of high temperature granite under different numbers of heating–cooling cycles. Combining a series of laboratory uniaxial compression tests with acoustic emission (AE) monitoring, it reveals the AE characteristics and damage behavior of high temperature granite in different damage stages. Increasing the number of heating–cooling cycles exponentially raised the mass-loss and volume-increase rates of the granite and exponentially decreased the P-wave velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The pore joint that is present in the rock specimen is compacted when the stress is greater than the rock's initial fracture stress. When the stress is continuously applied, new cracks gradually appear in the rock specimen, and the crack volumetric strain gradually increases [41]. The internal crack of the rock specimen is compressed during loading in the cycle of loading and unloading.…”
Section: Crack Volume Evolution Law Of Freeze-thaw Rock Under Cyclic ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The pore joint that is present in the rock specimen is compacted when the stress is greater than the rock's initial fracture stress. When the stress is continuously applied, new cracks gradually appear in the rock specimen, and the crack volumetric strain gradually increases [41]. The internal crack of the rock specimen is compressed during loading in the cycle of loading and unloading.…”
Section: Crack Volume Evolution Law Of Freeze-thaw Rock Under Cyclic ...mentioning
confidence: 99%
“…Cui et al [41], Song et al [47], and Niu et al [49] suggested that the RA and AF indices of the AE parameters can be used to study the evolution of shear and tensile cracks in rocks.…”
Section: Evolution Of Rupture Mode (Ra-af) During Cyclic Loading and ...mentioning
confidence: 99%
“…On the one hand, this property of rock, namely low temperature-induced thermal stress cracking, can be harnessed to fracture rocks and enhance mining efficiency. On the other hand, the thermal damage of rock mass caused by low temperature-induced thermal stress will also pose a certain threat to the safety and stability of surrounding rocks [12][13][14]. Therefore, in order to overcome the bottleneck of deep resource mining and investigate the causes and mechanisms of mining-induced disasters in deep rock masses more effectively, it is crucial to conduct a comprehensive study on the mechanical properties of high-temperature rocks subjected to rapid cooling cycles.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters provide information on the principal physical characteristics of AE hits, and much effort has been made to relate them to their sources. For example, the statistical distribution of hit amplitudes was used to identify cracks in rocks and concrete by applying the "b-value" method [15,16]; the cumulative counts and AE energy rates have been related to different damage stages on rock specimens under different test conditions [17,18]; the amplitude values have been related to the lubricant composition in the monitoring of wire drawing process [19]; and the cumulative AE energy is commonly used to evaluate fatigue damage in concrete beams [20]. These parameters provide information on the principal physical characteristics of AE hits, and much effort has been made to relate them to their sources.…”
mentioning
confidence: 99%